Presenting a Model for Predicting Body Image Concern in Female Bodybuilding Athletes Based on Basic Psychological Needs With the Mediating Role of Integrative Self-Knowledge - Kashiha, Shahla; Gholami Toranposhti, Marzieh; Ghamari, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to develop and test a structural model for predicting body image concern in female bodybuilding athletes based on basic psychological needs, considering the mediating role of integrative self-knowledge. Methods and Materials: This applied study adopted a descriptive–correlational design using structural equation modeling. The statistical population comprised all female bodybuilding athletes in Qazvin during 2024, from whom 375 participants were selected through available sampling. Data were collected using standardized questionnaires measuring body image concern, basic psychological needs, and integrative self-knowledge. Content validity was confirmed through expert review, and reliability was verified using Cronbach’s alpha and composite reliability coefficients. Descriptive analyses were conducted to examine data distribution, and inferential analyses were performed using SPSS 25 and LISREL 7.80 to test the measurement and structural models, evaluate model fit, and assess direct and indirect effects. Findings: Structural equation modeling indicated that basic psychological needs had a significant negative direct effect on body image concern and a significant negative effect on integrative self-knowledge. Integrative self-knowledge also showed a significant negative effect on body image concern. Mediation analysis revealed that integrative self-knowledge partially mediated the relationship between basic psychological needs and body image concern. The coefficient of determination demonstrated substantial explained variance for body image concern, and goodness-of-fit indices, predictive relevance, and discriminant and convergent validity measures confirmed the adequacy of the measurement and structural models. Conclusion: The findings indicate that satisfaction of basic psychological needs and higher levels of integrative self-knowledge play a crucial role in reducing body image concern among female bodybuilding athletes, supporting an integrative motivational–self-regulatory framework for understanding body image in physique-oriented sports.